INSPIRATION IN LEARNING: EFFORTS TO BUILD LEARNING ENTHUSIASM IN JUNIOR HIGH SCHOOL - Sutanto, Sutanto; Suhermanto, Suhermanto (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research explores and analyzes the learning strategies and approaches used at SMP NU 07 Wringin Bondowoso to form students' enthusiasm for learning. In the context of education in an era that continues to develop, it is essential to understand how a school can inspire and motivate students to excel academically and develop their potential. Researchers collected data through several stages, such as observation and direct observation at the research site. Interview interviewing several informants at the research location. This research methodology involved classroom observations, interviews with teachers, and analysis of documents related to the curriculum and learning programs at SMP NU 07. The data collected was then analyzed qualitatively to identify critical factors that support the formation of enthusiasm for learning at school. The research results show that SMP NU 07 Wringin Bondowoso carries a learning approach that applies Islamic values and Nahdlatul Ulama (NU) traditions on a moral and ethical basis. In addition, this school actively applies innovative and technology-based learning methods to increase student engagement. This learning program is designed to arouse interest in learning, increase creativity, and foster a spirit of leadership and entrepreneurship among students